THE ROLE OF ZAKAT AMIL INSTITUTIONS IN PRODUCTIVE ZAKAT UTILIZATION - Sri Wahyuni; Muhammad Nasrullah (Proceeding International Seminar of Islamic Studies, 2022)
This research is empirical legal research or known as non-doctrinal research. It is said so because this research examines the applicable law and has been implemented by the community or is called law in action. This study examines the role of the Medan zakat house as a zakat manager in the utilization of productive zakat. The research method used is qualitative, namely by describing the data and facts that appear in the research as they are and then analyzed using descriptive analytical and critical methods. Utilization of productive zakat at LAZ Rumah Zakat Medan Branch through Big Smile programs such as Free Maternity Homes (RBG), Circumcision Programs, then winning smiles such as the Sustainable Ceria Scholarship, SD-SMA, sustainable smiles such as Archipelago Nutrition Alert, Disaster Alert, Water Well Village.In implementing program, LAZ Rumah Zakat Medan faces obstacles including the Centralization of Zakat Management based on Law no. 23 of 2011, Public Awareness Regarding the Utilization of Productive Zakat, Aspects of reforming zakat from classical fiqh to modern understanding, Attitudes of Lack of Public Trust in LAZ, Efforts to Change Mustahik Status to Muzakki, Intensity of Counseling, Recruitment of Human Resources, No Firm Sanctions for People Who Reluctant Pay Zakat.Keywords: Productive Zakat, Muzakki and Mustahik